2017
DOI: 10.1371/journal.pone.0174296
|View full text |Cite
|
Sign up to set email alerts
|

Differences in STEM doctoral publication by ethnicity, gender and academic field at a large public research university

Abstract: Two independent surveys of PhD students in STEM fields at the University of California, Berkeley, indicate that underrepresented minorities (URMs) publish at significantly lower rates than non-URM males, placing the former at a significant disadvantage as they compete for postdoctoral and faculty positions. Differences as a function of gender reveal a similar, though less consistent, pattern. A conspicuous exception is Berkeley’s College of Chemistry, where publication rates are tightly clustered as a function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 16 publications
3
49
0
Order By: Relevance
“…Moreover, the few existing studies concerning graduate student sense of belonging are limited in scope. They either focus solely on understanding singular aspects of academic membership-such as publication rate [47], program structure [30], or mentoring and professional networks [42]-or rely on small interviewee populations to gather more information about factors that affect sense of belonging [45,46]. In addition, only a small number of studies have suggested practical ways to combat the factors that contribute to low sense of belonging in graduate communities.…”
Section: Motivationmentioning
confidence: 99%
“…Moreover, the few existing studies concerning graduate student sense of belonging are limited in scope. They either focus solely on understanding singular aspects of academic membership-such as publication rate [47], program structure [30], or mentoring and professional networks [42]-or rely on small interviewee populations to gather more information about factors that affect sense of belonging [45,46]. In addition, only a small number of studies have suggested practical ways to combat the factors that contribute to low sense of belonging in graduate communities.…”
Section: Motivationmentioning
confidence: 99%
“…About a dozen years ago, Nettles and Millett (2006) reported that African-American graduate students publish significantly less than their peers. Similarly, a recent study found that URM students submitted fewer papers than whites and Asians ( Mendoza-Denton et al. , 2017 ).…”
Section: Publications By Graduate Studentsmentioning
confidence: 88%
“…Recent studies have found that to increase the proportion of underrepresented minority (URM) faculty, graduate and postdoctoral training programs should focus efforts on the transition from trainee to faculty ( 47 , 48 ) . To improve this transition, the life science education and research fields must begin to consider interventions that can address the career-development of future faculty: " we must broaden the focus of professionalization and rectify the imbalance between training for research and training for a career" (49,50) . In recent years, some interventions have been used to supplement the research faculty mentoring role, and multiple governmental funding mechanisms aimed at supporting the needs of trainees with diverse backgrounds and diverse career goals ( 51 -55 ) .…”
Section: Impact On the Diversification Of The Academic Pipelinementioning
confidence: 99%